Social Entrepreneurial Intention: A Systematic Literature Review and Research Agenda - Prayoga, Bintang Eko Dwi; Susilaningsih, Susilaningsih; Indriayu, Mintasih (Universitas Islam Kadiri, 2024)
Social entrepreneurial intention (SEI) concepts are an urgently growing study area. The rising proportion of research used the entrepreneurial intention model as a well-grounded theoretical framework. Nevertheless, most of these studies need more systematicity and categorization, and there is a tendency to initiate new research in each study. Accordingly, there is a need to review the current knowledge in the area. Then, this paper conducts a literature review on SEI to identify publication trends and the specific themes under study within each category in this research area. Consequently, this paper analyzes 73 papers about SEI published from 2013–2023 in the Scopus database focusing on Q1 and Q2 accredited international journals. Specifically, the 73 papers were divided into four primary research categories: core social entrepreneurial intention models; personal-level variables; entrepreneurship education; and context and institutions. This paper seeks to fill the gap in existing research and literature on SEI, which is important for academics, professionals, and policymakers through the categorization of SEI that has been discussed in this study.